Abundance estimates of an isolated population of common bottlenose dolphins Tursiops truncatus in Walvis Bay, Namibia, 2008-2012 - Elwen, SH; Leeney, RH; Gridley, T (African journal of marine science, 2019)
The coastal population of common bottlenose dolphins Tursiops truncatus found in Namibia is regionally isolated and unique. This population faces several potential anthropogenic threats, especially in Walvis Bay, including boat-based tourism, a commercial harbour undergoing expansion, and aquaculture for oysters and mussels. Between 2008 and 2012, 238 boat-based surveys were conducted, resulting in 170 encounters with bottlenose dolphins. Overall, group sizes varied from 1 to 45 individuals (mean 10.7). Encounter rates, group sizes and total numbers of animals identified were higher in winter than in summer field seasons. The number, and survival and immigration parameters, of bottlenose dolphins using Walvis Bay was investigated using robust design and Huggins closed-population mark-recapture models. The highest numbers estimated were in the first and last years of the study, with estimates of 74-82 in 2008 and 76-77 in 2012 (numbers identified and upper 95% confidence limits). The only previously available data, from an incomplete study in the early 1990s, suggested that the population was between 100 and 150 individuals at the time. Although no linear trend in population size was obvious during the current study, the clear evidence of isolation, small population size, low annual birth rate, and potential long-term decrease in numbers since the early 1990s is concerning. Further work to collect data on demographic parameters is urgently recommended with a view to obtaining increased protection for this species.